Caffeic Acid Phenethyl Ester Prevents Colitis-Associated Cancer by Inhibiting NLRP3 Inflammasome - Dai, Guoliang; Jiang, Zhitao; Sun, Bingting; Liu, Chao; Meng, Qinghai; Ding, Kang; Jing, Wen; Ju, Wenzheng (Frontiers in Oncology, 2020)
Long-lasting inflammation in the intestinal tract renders individuals susceptible to colitis-associated cancer (CAC). The NOD-like receptor protein 3 (NLRP3) inflammasome plays a key role in the progression of inflammatory bowel disease and CAC. Therefore, identifying effective drugs that prevent CAC by targeting NLRP3 inflammasome is of great interest. Here, we aimed to evaluate the anti-inflammatory effect of caffeic acid phenethyl ester (CAPE) on bone marrow-derived macrophages (BMDMs), THP-1 cells, and azoxymethane/dextran sulphate sodium (AOM/DSS)-induced colon cancer mouse model. We also investigated the anti-tumour mechanism of CAPE. We found that CAPE decreased NLRP3 inflammasome activation in BMDMs and THP-1 cells and protected mice from colorectal cancer induced by AOM/DSS. CAPE regulated NLRP3 at the post-transcriptional level by inhibiting reactive oxygen species (ROS) production. However, CAPE did not affect NLRP3 or IL-1β transcription, but instead enhanced NLRP3 binding to ubiquitin molecules, promoting NLRP3 ubiquitination and contributing to the anti-tumour effect in the AOM/DSS mouse model. Moreover, CAPE suppressed the interaction between NLRP3 and CSN5 but enhanced that between NLRP3 and Cullin1 both in vivo and in vitro. Altogether, our findings demonstrate that CAPE prevents CAC by post-transcriptionally inhibiting NLRP3 inflammasome. Thus, CAPE may be an effective candidate for reducing the risk of CAC in patients with inflammatory bowel disease.